Dinamika Psychological Empowerment pada Komunitas Perempuan Pelaku Usaha: Studi Kualitatif - Salsabilla Fatin; Dian Nabila Septiani; Alifia Herman; Ilham Pramudya; Siti Hikmah (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
This study aims to explore the dynamics of psychological empowerment among women entrepreneurs by examining how they construct entrepreneurial identity, develop competence, cultivate independence, and generate social impact through their business activities. The background of this research stems from the need for women in micro and small enterprises to receive support that extends beyond technical skill development, emphasizing psychological aspects such as self-belief, personal control, and decision-making capacity. Employing a qualitative phenomenological approach, this study involved three women entrepreneurs selected through purposive sampling. Data were collected using semi-structured interviews to capture the participants’ subjective experiences in managing their businesses. The findings reveal four central themes: entrepreneurial identity shaped by personal values and lived experiences, competence that evolves through continuous learning and problem-solving, independence reflected in decision-making and business management, and social impact manifested in the creation of economic opportunities and contributions to the surrounding community. These results illustrate that psychological empowerment among women entrepreneurs is a dynamic process formed through the interaction of personal experiences, entrepreneurial practices, and community support. The study emphasizes the importance of empowerment programs that integrate psychological strengthening alongside technical training, with communities serving as vital spaces for collective learning and mutual support. Recommendations highlight the need for holistic empowerment models that consider the sociocultural context of women entrepreneurs and foster sustainable growth in both personal and business capacities.